Addressing the social costs of international migration to Filipino families and children - Anonuevo, Augustus T. (UP Los Baños Journal, 2010)
International migration, albeit its benefits, has its social costs. With the feminization of international migration, it is expected that separation from migrant mothers would adversely affect a large number of families and children in the country. Empirical studies conducted on the social costs of migration in the country focused on the effects on children left behind by their migrant parents. These studies revealed some conflicting findings but were unanimous on the adverse effects of the physical abscence of migrant mothers on their children's emotional well-being, school performance and relationships with parents.